ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INVESTASI SWASTA DI BEBERAPA NEGARA DI ASEAN - Titin Yulida; Syamsul Amar B; Melti Roza Adry (Universitas Negeri Padang, 2019)
This study aims to analyze the effects of: interest rates on private investment in ASEAN, inflation rates on private investment in ASEAN, exchange rates on private investment in ASEAN, output on private investment in several countries in ASEAN. This type of research is descriptive research. The data in this study are secondary data. The data analysis technique used is descriptive analysis and inductive analysis and hypothesis t test and f test. The results showed that the interest rate had a positive and not significant effect on private investment (Y), inflation had a negative and not significant effect on private investment (Y), the exchange rate had a negative and significant effect on private investment (Y), and output had a positive and significant effect towards private investment (Y).